2013
DOI: 10.1620/tjem.229.245
|View full text |Cite
|
Sign up to set email alerts
|

The -308G/A Polymorphism of the Tumor Necrosis Factor-alpha Gene Is Associated with the Risk of Upper Aerodigestive Tract Cancer: A Meta-analysis

Abstract: Tumor necrosis factor-alpha (TNF-α ) has been proposed to contribute to the development of upper aerodigestive tract (UADT) cancer that is characterized by poor prognosis. The G-to-A nucleotide change at -308 of the TNF-α gene (-308G/A polymorphism) can increase the expression level of TNF-α and thus may affect the genetic susceptibility of UADT cancer. The association between the -308G/A polymorphism and UADT cancer has been widely studied, but the results published are quite controversial. To obtain a more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
(50 reference statements)
1
4
0
1
Order By: Relevance
“…We found that an increased overall SCC risk was associated with the rs1800629 polymorphisms in the Asian population under AA vs GG, and AA vs GG+GA models, but not A vs G, GA vs GG, GA+AA vs GG, or carrier A vs G models. A significant difference between LSCC/OSCC risks and the rs1800629 polymorphism was found under the AA vs GG, and AA vs GG+GA models; this corresponds with previous data on the link of rs1800629 and the risk of upper aero-digestive tract or head/neck SCC [ 25 , 26 ]. However, in 2013, Chen et al performed a meta-analysis to analyze the association between rs1800629 and oral cancer, and observed a negative association between rs1800629 and OSCC [ 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…We found that an increased overall SCC risk was associated with the rs1800629 polymorphisms in the Asian population under AA vs GG, and AA vs GG+GA models, but not A vs G, GA vs GG, GA+AA vs GG, or carrier A vs G models. A significant difference between LSCC/OSCC risks and the rs1800629 polymorphism was found under the AA vs GG, and AA vs GG+GA models; this corresponds with previous data on the link of rs1800629 and the risk of upper aero-digestive tract or head/neck SCC [ 25 , 26 ]. However, in 2013, Chen et al performed a meta-analysis to analyze the association between rs1800629 and oral cancer, and observed a negative association between rs1800629 and OSCC [ 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…Several meta-analyses studies have shown a moderate to strong association of TNF-α-308G/A SNP with an increased risk of and in many cases the progression of various cancers including hepatocellular carcinoma ( Feng et al, 2014 , Hu et al, 2014 ), prostate cancer ( Ma et al, 2014 ), oral cancer ( Yapijakis et al, 2009 ), lung cancer ( Peng et al, 2012 , Shih et al, 2006 ), cervical cancer ( Pan et al, 2012 , Zhang and Zhang, 2013 ), gastric cancer ( Gorouhi et al, 2008 , Hong et al, 2013 , Lu et al, 2010 , Zhang et al, 2008 ), esophageal cancer ( Wang et al, 2013 ), breast cancer ( Wang et al, 2011 , Yang et al, 2011b ) and colorectal cancer ( Chen et al, 2013 , Min et al, 2014 ). At the protein level, high plasma levels of TNF-α has been found in cancer patients and these high plasma levels have been associated with a poor prognosis in various cancers ( Abrahamsson et al, 1993 , Nakashima et al, 1998 ) including CRC ( Balkwill, 2002 ).Various studies have demonstrated the role of TNF-α as a key player in the progression of human CRC ( Balkwill, 2002 , Sharma et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The methods used for literature search and data extraction has been described elsewhere [41]. In brief, With the term “(cancer or carcinoma) and (Hypoxia-inducible factor-1α or HIF-1α) and (Polymorphism or mutation or variant)”, we found 35 reference in the PubMed, Embase and China National Knowledge Infrastructure (CNKI) database that were published after the first report on HIF-1α(last update: August 23 2013).…”
Section: Methodsmentioning
confidence: 99%